2012
DOI: 10.1186/1477-7827-10-97
|View full text |Cite
|
Sign up to set email alerts
|

Immunoregulation of follicular renewal, selection, POF, and menopause in vivo, vs. neo-oogenesis in vitro, POF and ovarian infertility treatment, and a clinical trial

Abstract: The immune system plays an important role in the regulation of tissue homeostasis ("tissue immune physiology"). Function of distinct tissues during adulthood, including the ovary, requires (1) Renewal from stem cells, (2) Preservation of tissue-specific cells in a proper differentiated state, which differs among distinct tissues, and (3) Regulation of tissue quantity. Such morphostasis can be executed by the tissue control system, consisting of immune system-related components, vascular pericytes, and autonomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
73
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(75 citation statements)
references
References 153 publications
(339 reference statements)
2
73
0
Order By: Relevance
“…We speculate that this hypothesis can be upgraded with the factor of location in the granulosa layers. Moreover, the question whether granulosa stem cells originate from the first line of flattened GCs in the primordial follicle or from the granulosa nests in ovarian surface epithelium [7] still remains opened.…”
Section: Expression Of Stem Cell Markers In Granulosa Cells From Follmentioning
confidence: 99%
“…We speculate that this hypothesis can be upgraded with the factor of location in the granulosa layers. Moreover, the question whether granulosa stem cells originate from the first line of flattened GCs in the primordial follicle or from the granulosa nests in ovarian surface epithelium [7] still remains opened.…”
Section: Expression Of Stem Cell Markers In Granulosa Cells From Follmentioning
confidence: 99%
“…In addition, researchers also found that with increasing age, the immune system inevitably degraded. First, the thymus function declines followed by a decline in ovarian function [27]. These results demonstrate that there is a close relationship between the immune system and the ovarian function.…”
Section: Factors Related To Ovarian Stem Cell Nests Agingmentioning
confidence: 94%
“…The conclusions are based on the following phenomenon of ovarian [27-29]: the immune relevant cells in the ovary rete tunnels, are necessary for the formation of ovary by OGSCs. Human embryonic ovary is determined by the evolution of the ovarian stem cells in the genital ridge peritoneal mesothelium, formed from the rete ovary in the mesonephric duct.…”
Section: The Composition and The Biological Characteristics Of Ovariamentioning
confidence: 99%
“…The OSE was supposed to be a source of germ cells, and new primordial follicles were developed by the accumulation of oocytes with nests of primitive granulosa cells in the ovarian cortex (Bukovsky et al, 1995). In 2005, a study of the possibility of neooogenesis and granulosa cell generation was done on cultures derived from the surface epithelium of adult human ovaries (Bukovsky et al, 2005).…”
Section: The Ovarian Surface Epithelium As a Source Of Germline Stem mentioning
confidence: 99%